MANAJEMEN PEMBELAJARAN AKTIF DAN EFEKTIF BERBASIS ROLE MODEL PADA GENERASI MILLENIAL - Ruaifatul Labibah; Sobri Washil; Mohammad Rifa'i (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2018)
ABSTRACT Learning is the center of teaching and learning activities consisting of educators and students who aim to realize intellectual maturity, emotional maturity, spiritual elevation, life skills, and moral greatness of students, so that learning activities are more effective and the material delivered can be mastered by participants the students need a change in the learning process carried out by a teacher. The focus of this research problem is to find out how to manage the application of active and effective learning models in achieving learning objectives. This study aims to describe the extent to which the application of active learning models and effective learning in achieving learning goals in the cognitive, affective, and psychomotor domains. The results of the study can be concluded that broadly the application of active and effective learning models in achieving learning objectives has been implemented well, namely in the cognitive domain applied methods included in the active and effective learning models such as the question and answer method, memorization, debate, and contributing suggestions . In the affective domain, the method of group discussion and recitation is applied (group collaboration). In the psychomotor realm, a drill or training method is applied.